Triethyl orthobenzoate in reactions with primary amines and sodium azide - Grigoriev, Yuri V.; Grigoriev, Evgeny Y.; Ivashkevich, Ludmila S.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2023)
The reaction of triethyl orthobenzoate with primary amines and sodium azide has been studied. It has been established that, in contrast to the orthoesters of formic, acetic and monochloroacetic acids, whose heterocyclisation with primary amines and sodium azide leads to the formation of 1- and 1,5-substituted tetrazoles, triethyl orthobenzoate does not form corresponding 1-substituted 5-phenyltetrazoles under analogous conditions. The main reaction products are N-substituted benzamides. When ethylenediamine or diethylenetriamine is used as primary amine, the main reaction products are hydrolysis-resistant cyclic amidines, namely 2-phenyl-4,5-dihydroimidazole and N-(2-(2-phenyl-4,5-dihydroimidazol-1-yl)ethyl)benzamide, respectively. The obtained data indicate that the azide ion does participate in the reaction under study.
Keywords: triethyl orthobenzoate; primary amines; N-substituted benzamides; benzamidines; synthesis